Learning Groovy - Davis, Adam L. (Apress, 2016)
Start building powerful apps that take advantage of the dynamic scripting capabilities of the Groovy language. This book covers Groovy fundamentals, such as installing Groovy, using Groovy tools, and working with the Groovy Development Kit (GDK). You'll also learn more advanced aspects of Groovy, such as using Groovy design patterns, writing DSLs in Groovy, and taking advantage of Groovy's functional programming features. There is more to Groovy than the core language, so Learning Groovy covers the extended Groovy ecosystem. You'll see how to harness Gradle (Groovy's build system), Grails (Groovy's web application framework), Spock (Groovy's testing framework), and Ratpack (Groovy's reactive web library). What You'll Learn Grasp Groovy fundamentals, including the GDK or Groovy Development Kit Master advanced Groovy, such as writing Groovy DSLs Discover functional programming in Groovy Work with GPars, the built-in concurrency library Use Gradle, the build system Master Grails, the web application framework Work with Spock, the testing framework Harness Ratpack, the reactive web library Who This Book Is For Although this book is intended for those with a Java background, anyone with basic programming skills could benefit from it. This book is a data-filled, yet easy-to-digest tour of the Groovy language and ecosystem.